EFEKTIFITAS PIJAT REFLEKSI KAKI DAN HIPNOTERAPI TERHADAPPENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - nugroho, irmawan andri; -, asrin; -, sarwono (LPPM STIKES MUHAMMADIYAH GOMBONG, 2012)
Therapeutic of reflexology and hypnotherapy has not been knownand developed for nursing implementation in Indonesia. One of thebenefits of both therapies is to reduce blood pressure of hypertensionpatients.This study aimed to know the difference between theeffectiveness of foot reflexology massage therapy and hypnotherapy todecrease blood pressure of hypertension patients.The study was quasi experiment. The samples in this study were60 respondents, consisting of 30 respondents in each group of footreflexology and 30 respondents of hypnotherapy. Blood pressure wasmeasured by using a sphygmomanometer. The method of analyze data isuse descriptive quantitative method.Statistical analysis with Mann Whitney U-test found Sig.reflexology foot massage is 0.000, and hypnotherapy 0.001 showed thatSig. <0.05, which means there is a difference between foot reflexologymassage and hypnotherapy significantly. The mean rank of reflexology is40.00 and hypnotherapy 35.50 showing foot reflexology massage is moreeffective than hypnotherapy.There is a difference of effectiveness between foot reflexology andhypnotherapy in reducing blood pressure of hypertension patients.Reflexology foot massage is more effective than hypnotherapy in reducingblood pressure of hypertension patients.Keywords: Foot Reflexology massage, hypnotherapy, blood pressure,hypertension